GENDER DIFFERENCES IN THE STRATEGY INVENTORY FOR LANGUAGE LEARNING (SILL) - Serliah Nur; Faidah Yusuf (IJEE (Indonesian Journal of English Education), 2022)
ABSTRACTThis research investigates the learning strategies used by English as a foreign language (EFL) students and gender differences in the strategy inventory for language learning (SILL) in Indonesia. To gather the data, this study employed quantitative descriptive methods with a Google form-based questionnaire involving 110 college students, and the data were analysed using SPSS 25. The fifty items of the questionnaire were divided into six strategies: memory strategy, cognitive strategy, metacognitive strategy, compensation strategy, emotion strategy, and social strategy. Findings of the study indicate that the students use all the strategies in learning English, and all these strategies are in a high level of use except for memory strategy which is in a moderate level. Gender differences data show that most male students preferred the social strategy (36%), whereas most female students preferred metacognitive strategy (56.47%) suggesting that male and female students have different learning styles. The results of this research shed light on the importance of raising teachers’ awareness of their students’ diversity in learning strategies. Thus, teachers should improve their repertoire of teaching techniques and strategies to meet students’ different learning styles in the classroom. ABSTRAKPenelitian ini menyelidiki strategi pembelajaran yang digunakan oleh siswa bahasa Inggris sebagai bahasa asing (EFL) dan perbedaan gender dalam inventarisasi strategi untuk pembelajaran bahasa (SILL) di Indonesia. Untuk mengumpulkan data, penelitian ini menggunakan metode kuantitatif dengan kuesioner berbasis Google form yang melibatkan 110 mahasiswa, dan data dianalisis menggunakan SPSS 25. Lima puluh item kuesioner dibagi menjadi enam strategi: strategi memori, strategi kognitif, strategi metakognitif. strategi, strategi kompensasi, strategi emosi, dan strategi sosial. Temuan penelitian menunjukkan bahwa siswa menggunakan semua strategi dalam belajar bahasa Inggris, dan semua jenis strategi berada di tingkat tinggi kecuali strategi memori yang berada di tingkat sedang. Data perbedaan gender menunjukkan bahwa sebagian besar siswa laki-laki lebih menyukai strategi sosial (36%), sedangkan sebagian besar siswa perempuan lebih menyukai strategi metakognitif (56,47%) menunjukkan bahwa siswa laki-laki dan perempuan memiliki gaya belajar yang berbeda secara signifikan. Hasil penelitian ini menyoroti pentingnya meningkatkan kesadaran guru tentang keragaman siswa mereka dalam strategi pembelajaran. Dengan demikian, guru harus meningkatkan repertoar teknik dan strategi pengajaran mereka untuk memenuhi gaya belajar siswa yang berbeda di kelas.